Unveiling the greenhouse gas emissions of drinking water treatment plant throughout the construction and operation stages based on life cycle assessment - Peng Zhang; Boru Ma; Guolu Zheng; Fukuan Li; Wei Zhang; Jingwen Gu; Zehong Liu; Kexun Li; Hao Wang (Ecotoxicology and Environmental Safety, 2024)
The carbon peaking and carbon neutrality targets proposed by the Chinese government have initiated a green transformation that is full of challenges and opportunities and endowed sustainable development strategy for combating global warming issue. It is essential to execute comprehensive identification and carbon reduction measures across all industries that produce greenhouse gas (GHG) emissions. Water supply system, as an energy-intensive sector, plays a crucial role in GHG reduction. This work conducted a life cycle assessment (LCA) to account the GHG emissions associated with the construction and operation phases of the drinking water treatment plant (DWTP). During the construction phase, the total GHG emissions were 19,525.762 t CO2-eq, with concrete work and rebar project being the dominant contributors (87.712%). The promotion of renewable or recyclable green building materials and low-carbon construction methods, such as the utilization of prefabricated components and on-site assembly, holds significant importance in reducing GHG emissions during the construction phase of DWTP. Regarding the operation stage, the DWTP possessed an average annual GHG emission of 37,660.160 t CO2-eq and an average GHG intensity of 0.202 kg CO2-eq/m3. Most emissions were attributed to electricity consumption (67.388%), chemicals utilization (12.893%), and heat consumption (10.414%). By increasing the use of clean energy and implementing strict control measures in the water supply pumps, energy consumption and GHG emissions can be effectively reduced. This study offers valuable insights into the mapping of GHG emissions in the DWTP, facilitating the identification of key areas for targeted implementation of energy-saving and carbon-reducing measures.